Food emulsion type oil in water prepared with high-protein from shrimp (Penaeus vannamei) heads flour – SHF (2017)
The use of flour from shrimp (Penaeus vannamei) heads with a high content of protein (SHF) to stabilize food emulsions type oil in water (o/w) is an alternative to take advantage of the by-products of the shrimp industry. The aim of this work was to prepare food emulsion type oil in water (o/w) using the SHF due to the high percentage in proteins; for this procedure a physicochemical and bromatological characterization of flour of shrimps (Penaeus vannamei) heads has been done, in which a percentage of protein 51 %, moisture of 11,82 %, fat 8,52 % and 22,23 % of ash has been obtained. The base emulsions may be used in food products such as salad dressing, mayonnaise, spreads, dressings and other products. The different emulsions with adequate rheological and microstructural characteristics were prepared using different concentrations of palm oil (20, 30 and 40%w/w) and different concentrate of SHF (0,5, 1 and 2 % w/w). Therefore, we have obtained a food emulsion stable type oil in water (O/W) with 2 % w/w of SHF, which presented a behavior non-Newtonian fluid type shear-thinning and homogeneous distribution of droplets.